Heat and mass transfer - Rolle, Kurt C. (Cengage Learning, 2016)
Thoroughly up-to-date and packed with real world examples that apply concepts to engineering practice, HEAT AND MASS TRANSFER, 2e, presents the fundamental concepts of heat and mass transfer, demonstrating their complementary nature in engineering applications. Comprehensive, yet more concise than other books for the course, the Second Edition provides a solid introduction to the scientific, mathematical, and empirical methods for treating heat and mass transfer phenomena, along with the tools needed to assess and solve a variety of contemporary engineering problems. Practical guidance throughout helps students learn to anticipate the reasonable answers for a particular system or process and understand that there is often more than one way to solve a particular problem. Especially strong coverage of radiation view factors sets the book apart from other texts available for the course, while a new emphasis on renewable energy and energy efficiency prepares students for engineering practice in the 21st century.